WILD MAMMALS OF ANCIENT NORTH CHINA. Issue 2 (2nd April 2018) - Lander, Brian; Brunson, Katherine
Abstract: Human activity has eliminated many of the natural lowland ecosystems of the Middle and Lower Yellow River Valley, and has modified the rest, making it difficult to understand what species are native to the region. As a step towards the reconstruction of these lost environments, this paper employs zooarchaeological and other evidence to identify the native mammals of the region. We provide basic ecological information about these animals and discuss controversial or difficult cases in more depth. Our goal is not only to study China's environmental history, but also to make clear that conventional understandings of species ranges are based on the distributions of animals in the modern period, when many had already been eliminated from large areas by human activity.